(untitled) (Philology, 2026)
The paper analyzes the romanticist macro and micro-universes of imprisonment, as compensatory to the real world: monastery-cell, island-cave. The literary production of Mihai Eminescu is a unity of themes, literary motives, concepts, general vision – which exist in the poetry, prose, and dramatic literature. The hypostasis of the Genius thinker, usually incarnate by an artist, a prince, a monk – are in the novel Cézara in fusion, interested in recovering the fabulous couple, or the fulfillment through love. These general-romanticist themes are particularized by some specific literary leitmotivs (the lake, the moon, the night, the ruins, the cliffs, and the lush nature), and the space is analyzed through the ideas of Bachelard, Sloterdijk, Deleuze, Durand.